Psychology and Pathophysiological Outcomes of Eating - Takada, Akikazu; Himmerich, Hubertus (IntechOpen, 2021)
The psychology of eating is regulated by neural mechanisms. When not well controlled, eating may result in disorders and health hazards such as obesity, type 2 diabetes mellitus, and vascular diseases. Lifestyles and cultures influence eating habits, thus there are differences in the prevalence of health problems depending upon living environments. This book examines the psychology and the pathophysiological outcomes of eating. Chapters address such topics as the influence of lifestyle, circadian rhythm, sleep, and fragrant odors on appetite and weight regulation; the impact of glucose, sucrose, lactate, and ketone bodies on the brain; the consequences of glycation stress on the skeletal muscle; and much more.